Flood potential estimation of two small vegetated watersheds - Katimon, Ayob; Mohd. Yunos, Mohd. Zulkifli (Faculty of Civil Engineering, UTM, 2003)
Real-time (observed) rainfall-runoff data from two small watersheds was use to estimate the flood potential of the area. The first watershed (W-1) is located in a hilly area near Serdang, Selangor. The second watershed (W-2) is a flat land of peat soil located in Pontian, Johor. A SCS (Soil Conservation Service) curve number (CN) technique, which is, considered as one of the GIS-based empirical approach was used in the study to predict daily-event storm runoff. The predicted runoff obtained from SCS-CN technique was compared with those of the observed values and from conventional Rational method. The results show that the SCS-CN technique was over-predicted for cases in W-1 watershed. Conversely, the SCS-CN was under-predicted for W-2 watershed.